INTENSITAS MENGAKSES SITUS PORNO DAN PERILAKU SEKSUAL REMAJA - Endah, Fitriasary; Immawan Muslimin, Zidni (Universitas Ahmad Dahlan, 2009)
The purpose of this research was to know correlation between intensity for accessing porn sites and sexual behavior of adolescence. The hypotheses in this research have positive correlation between intensity of accesing porn sites and sexual behavior of adolescence. 77 Senior High School students were participated in this research. The data collected by intensity for accessing porn sites scale and sexual behavior scale. Pearson Product moment was used to analyze the data, which result correlation coefficient (r) : 0,440 and p <0,01. It means that there is positive correlation between intensity for accessing porn sites and sexual behavior of adolescence.